The Analysis of Entrepreneurial Activity in The Area of Brod-Posavina County for The Period from The Year 2014 to The Year 2018 (Vallis Aurea, 2020)
The main objective of this paper is to determine total investments by activities in Brod-Posavina County, revenues and expenditures level, number of entrepreneurs by activities, including the achieved financial results of entrepreneurs of the Brod-Posavina County over the past five years.During research of facts and possibilities that currently exist, the following research methods are used in a different combination: historical method, the method of analysis and synthesis, classification, description method and generalization.